Cumulative asbestos exposure and mortality from asbestos related diseases in a pooled analysis of 21 asbestos cement cohorts in Italy - Ferdinando Luberto; Daniela Ferrante; Stefano Silvestri; Alessia Angelini; Francesco Cuccaro; Anna Maria Nannavecchia; Enrico Oddone; Massimo Vicentini; Francesco Barone-Adesi; Tiziana Cena; Dario Mirabelli; Lucia Mangone; et al. (BMC, 2019)
Abstract Background Despite the available information on cancer risk, asbestos is used in large areas in the world, mostly in the production of asbestos cement. Moreover, questions are raised regarding the shape of the dose response relation, the relation with time since exposure and the association with neoplasms in various organs. We conducted a study on the relationship between cumulative asbestos exposure and mortality from asbestos related diseases in a large Italian pool of 21 cohorts of asbestos-cement workers with protracted exposure to both chrysotile and amphibole asbestos. Methods The cohort included 13,076 workers, 81.9% men and 18.1% women, working in 21 Italian asbestos-cement factories, with over 40 years of observation. Exposure was estimated by plant and period, and weighted for the type of asbestos used. Data were analysed with consideration of cause of death, cumulative exposure and time since first exposure (TSFE), and by gender. SMRs were computed using reference rates by region, gender and calendar time. Poisson regression models including cubic splines were used to analyse the effect of cumulative exposure to asbestos and TSFE on mortality for asbestos-related diseases. 95% Confidence Intervals (CI) were computed according to the Poisson distribution. Results Mortality was significantly increased for 'All Causes' and 'All Malignant Neoplasm (MN)', in both genders. Considering asbestos related diseases (ARDs), statistically significant excesses were observed for MN of peritoneum (SMR: men 14.19; women 15.14), pleura (SMR: 22.35 and 48.10), lung (SMR: 1.67 and 1.67), ovary (in the highest exposure class SMR 2.45), and asbestosis (SMR: 507 and 1023). Mortality for ARDs, in particular pleural and peritoneal malignancies, lung cancer, ovarian cancer and asbestosis increased monotonically with cumulative exposure. Pleural MN mortality increased progressively in the first 40 years of TSFE, then reached a plateau, while peritoneal MN showed a continuous increase. The trend of lung cancer SMRs also showed a flattening after 40 years of TSFE. Attributable proportions for pleural, peritoneal, and lung MN were respectively 96, 93 and 40%. Conclusions Mortality for ARDs was associated with cumulative exposure to asbestos. Risk of death from pleural MN did not increase indefinitely with TSFE but eventually reached a plateau, consistently with reports from other recent studies.